Antibacterial Activity of Ethanol Extracts of Sempur Air (Dillenia suffruticosa) and Akar Kaik-kaik (Uncaria cordata) Leaves Against Shigella dysentriae and Salmonella typhimurium - Syafriana, Vilya; Ramadhani, Lidia Anggita; Helma, Fitria; Ningsih, Wirna; Suyatno, Suyatno (Journal of Tropical Pharmacy and Chemistry, 2024)
Sempur air (Dillenia suffruticosa) and akar kaik-kaik (Uncaria cordata) are two plants that can be found on Sumatra, Indonesia. The locals employ those herbs as traditional medicine in variety of ways, including treating diarrhea. This study sought to confirm the efficacy of sempur air and akar kaik-kaik leaf extracts as traditional diarrhea remedies. Leaves were obtained in Bangka-Belitung and Riau, Sumatra. They were extracted with 70% ethanol as a solvent and then evaluated for the phytochemical constituents and antibacterial properties. The phytochemical screening found that the ethanol extract of akar kaik-kaik leaf contains alkaloids, tannins, and saponins, but no flavonoids or steroids/triterpenoids. The ethanol extract of sempur air leaf included alkaloids, flavonoids, tannins, and saponins; but neither steroids or triterpenoids. The ethanol extract of akar kaik-kaik leaf showed no impact on Shigella dysentriae and Salmonella typhimurium, whereas the ethanol extract of sempur air leaf could inhibit S. dysentriae but not S. typhimurium.